Medicinal plants in mitigating electromagnetic radiation-induced neuronal damage: a concise review. (2nd January 2022) - Raghu, Shamprasad Varija; Kudva, Avinash Kundadka; Rajanikant, Golgodu Krishnamurthy; Baliga, Manjeshwar Shrinath
ABSTRACT: Although the evidence is inconclusive, epidemiological studies strongly suggest that increased exposure to electromagnetic radiation (EMR) increases the risk of brain tumors, parotid gland tumors, and seminoma. The International Agency for Research on Cancer (IARC) has classified mobile phone radiofrequency radiation as possibly carcinogenic to humans (Group 2B). Humans being are inadvertently being exposed to EMR as its prevalence increases, mainly through mobile phones. Radiation exposure is unavoidable in the current context, with mobile phones being an inevitable necessity. Prudent usage of medicinal plants with a long history of mention in traditional and folklore medicine and, more importantly, are safe, inexpensive, and easily acceptable for long-term human use would be an appealing and viable option for mitigating the deleterious effects of EMR. Plants with free radical scavenging, anti-oxidant and immunomodulatory properties are beneficial in maintaining salubrious health. Green tea polyphenols, Ginkgo biloba, lotus seedpod procyanidins, garlic extract, Loranthus longiflorus, Curcuma amada, and Rosmarinus officinalis have all been shown to confer neuroprotective effects in validated experimental models of study. The purpose of this review is to compile for the first time the protective effects of these plants against mobile phone-induced neuronal damage, as well as to highlight the various mechanisms of action that are elicited to invoke the beneficial effects.